Performance of bile aspiration plus brushing to diagnose malignant biliary strictures during endoscopic retrograde cholangiopancreatography - Roth, Gael S. (Endosc Int Open, 2016)
Background and study aims: Endobiliary brushing during endoscopic retrograde cholangiopancreatography (ERCP) is the main technique used to diagnose a malignant stricture, but has a poor sensitivity. This study evaluated the diagnostic performance of bile aspiration associated with biliary brushing during ERCP to diagnose a malignant stricture, compared to brushing alone. Patients and methods: Between January 2007 and December 2012, all consecutive patients undergoing ERCP to treat a biliary stricture were included. After a biliary sphincterotomy, 3 mL to 10 mL of bile was aspirated into the brush catheter and collected in a dry sterile tube before and after brushing (to yield three samples). Brushing was performed as commonly recommended. Results: One hundred eleven patients (68 males, 43 females) were included; mean age 67 ± 15.4 years. A final diagnosis of malignant stricture was established in 51 patients, including 43 cholangiocarcinomas; 60 patients had benign strictures. Specificity (Sp) and positive predictive values were 100% for all samples. The diagnostic performance of the three-sample combination of bile aspiration + brushing + bile aspiration was significantly greater than brushing alone (P = 0.004): sensitivity (Se) = 84.3 % vs. Se = 66.7 %. The three-sample combination gave a negative predictive value of 88.2 %, and a diagnostic accuracy of 92.8 %. When suspicious results were added to malignant results as positive results, the three-sample combination gave Sp = 91.7 % and Se = 94.1 %. Conclusions: In cases of biliary stricture, conducting bile aspiration before and after brushing significantly increased the ability to diagnose a malignant stricture with a sensitivity of 84.3 % (P = 0.004).